The effects of bifrontal anodal transcranial direct current stimulation (tDCS) on sleepiness and vigilance in partially sleep‐deprived subjects: A multidimensional study - Alfonsi, Valentina; D'Atri, Aurora; Scarpelli, Serena; Gorgoni, Maurizio; Giacinti, Francesco; Annarumma, Ludovica; Salfi, Federico; Amicucci, Giulia; Corigliano, Domenico; De Gennaro, Luigi (Journal of sleep research, 2023)
Summary In recent years, transcranial electrical stimulation techniques have demonstrated their ability to modulate our levels of sleepiness and vigilance. However, the outcomes differ among the specific aspects considered (physiological, behavioural or subjective). This study aimed to observe the effects of bifrontal anodal transcranial direct current stimulation. Specifically, we tested the ability of this stimulation protocol to reduce sleepiness and increase vigilance in partially sleep‐deprived healthy participants. Twenty‐three subjects underwent a within‐subject sham‐controlled stimulation protocol. We compared sleepiness and vigilance levels before and after the two stimulation conditions (active versus sham) by using behavioural (reaction‐time task), subjective (self‐report scales) and physiological (sleep‐onset latency and electroencephalogram power [n = 20] during the Maintenance of Wakefulness Test) measures. We showed the efficacy of the active stimulation in reducing physiological sleepiness and preventing vigilance drop compared with the sham stimulation. Consistently, we observed a reduction of perceived sleepiness following the active stimulation for both self‐report scales. However, the stimulation effect on subjective measures was not statistically significant probably due to the underpowered sample size for these measures, and to the possible influence of motivational and environmental factors. Our findings confirm the ability of this technique to influence vigilance and sleepiness, pointing out the potential for new treatment developments based on transcranial electrical stimulation.